Patterns of athlete medication use at the 2018 PyeongChang Paralympic Games. A descriptive cohort study - Alexander, L. A.; Eken, M. M.; Teoh, C. S.; Stuart, M. C.; Derman, E. W.; Blauwet, C. A. (American Journal of Physical Medicine & Rehabilitation, 2022)
Objective: Medication use among elite athletes has received growing attention over the past decades. However, only limited studies have focused on para athletes, and trends in medication use among this cohort remain unclear. The aims of this study were (1) to describe the pattern of medication use in elite Paralympic athletes, with a particular focus on analgesics, (2) to analyze whether medications declared by athletes were included in the 2018 World Anti-Doping Agency`s prohibited list and monitoring program, (3) to report on a variety of novel supplements, and (4) to review whether athlete analgesic needs will be met by the new Olympic & Paralympic Model Formulary. Design: This is a retrospective, descriptive cohort study. Results: Of all athletes who underwent doping control, 21% declared the use of an analgesic medication. Athletes with limb deficiency and para snowboarders declared the most analgesic medications in their respective categories. It was determined that 84% of the athletes` analgesic medication needs were provided from the new Olympic & Paralympic Model Formulary. Conclusions: Analgesic use among athletes who participated at the 2018 PyeongChang Winter Paralympics was high. Para snowboarders and athletes with limb deficiency declared the most analgesics. The new Olympic & Paralympic Model Formulary adequately addressed the medication needs of the athletes attending the 2018 games.